Manpower Policy : Nature, Objectives, Perspectives - Meltz, Noah (Relations industrielles / Industrial Relations, 1969)
This article is intended to provide an overall view of the manpower field. A conceptual framework is developed for examining the various strands of the manpower field and the major government manpower programs are fitted into this framework. Suggestions for future manpower policies are also related to this framework.